The effect of hand dominance on neuromuscular monitoring at the adductor pollicis muscle - Jeong, Ji Seon; Kim, Kyo Sang; Lee, Hee Jong; Shim, Jae Chul; Lee, Jong Chul; Lee, Jeoung Hyuk (Korean journal of anesthesiology, 2013)
Neuromuscular blockade of the adductor pollicis muscle may be influenced by hand dominance resulting in conflicting results of several studies. The current study examined whether hand dominance could influence the measurements of neuromuscular blockade with acceleromyography at the adductor pollicis. The acceleromyographic responses from 0.6 mg/kg of rocuronium were monitored supramaximally in both hands in 31 patients after induction of anesthesia. Onset, maximum effect, and offset of rocuronium were measured and compared in both hands. The train-of-four (TOF) ratios to 0.9 were recorded in all patients. In total, 27 patients were right-handed and 4 patients were left-handed. The mean supramaximal threshold or initial TOF ratio was not different between dominant and nondominant hands. No statistically significant differences were found between 716 paired TOF ratios in both hands. A correlation was seen between the dominant and nondominant hand (Nondominant = 0.931·Dominant + 1.714, R = 0.929). The analysis by the Bland-Altman plot showed an excellent agreement with a bias of 1.6% and limits of agreement of -21.2 to 24.5%. Dominant and nondominant hands can be used interchangeably for neuromuscular monitoring at the adductor pollicis.